MENINGKATKAN LITERASI KESEHATAN MELALUI MEDIA POP UP BOOK BAGI ANAK DINI: IMPROVING HEALTH LITERACY ABILITY FROM DIGITAL POP UP BOOK MEDIA FOR EARLY CHILDREN - ELISABETH TAMPUBOLON; AHMAD FACHRURRAZI; ERVIN NURUL AFFRIDA; NITASIH INDAHSARI (incrementapedia, 2023)
Early childhood education level requires readiness from various elements, one of which is through a literacy program health that aims to help children understand the importance of behavior clean and healthy living (PHBS). The PHBS referred to is in the form bring supplies and do not share food as an effort to prevent Covid-19 at school. This research was carried out using the development method refers to research and development steps according to Borg & Gall (1983). The research objective is to develop pop up book media digital-based to improve health literacy skills in children aged 4-6 years. Product trial results consisting of media expert trials, substance experts trials, prospective users trials and tests field. The media expert test results obtained 85.83%, the substance expert test obtained the average 88.94%, and the test results for prospective product users obtained an average of 86.98%. it can be concluded that ABBA's pop up book media is very good and unnecessary revised. The results of the product effectiveness test obtained an average pre-test score (XB) of 1682 and the average post test score (XA) is 1811 when compared to the t table value at a significance level of 5% then 0.004 <0.05 so it can be concluded that pop up book media can improve health literacy skills in children aged 4-6 years.